Preserved learning despite impaired short-term memory in older adults with mild cognitive impairment - Smith, Elaina; Cortez, Christopher; Wiechmann, April; Davis, Sandra; Dyson, Hannah; Kucharski, Krystyn; Ross, Sarah; Kline, Geoffrey; Mallet, Robert T.; Shi, Xiangrong (Frontiers in Aging Neuroscience, 2025)
BackgroundThe impact of amnestic mild cognitive impairment (aMCI) on short-term memory (STM) and learning performance assessed with different memory modalities was unknown. This study examined differences in STM and learning ability between verbal and visuospatial memory-modalities in older adults with aMCI.MethodsThirty-nine aMCI subjects (71.5 ± 6.0 yrs) and 33 non-MCI (control) subjects (71.1 ± 5.7 yrs) of similar age and educational attainment consented to participate in the study. Short-term memory was assessed using Digit-Span-Test (DST), California-Verbal-Learning-Test-2nd edition – short-form (CVLT-II), and Brief-Visuospatial-Memory-Test-Revised (BVMT-R); CVLT-II and BVMT-R assessed verbal-and visuospatial-learning, respectively.ResultsDST-Backward (p = 0.016) and DST-Sequencing (p < 0.001) scores were significantly lower in the aMCI vs. control subjects (Student’s t-test), but DST-Forward scores did not differ (p = 0.237). Immediate and delayed free-recall scores in both CVLT-II (p < 0.001) and BVMT-R (p < 0.001) were lower in the aMCI subjects. The immediate free-recall scores in both tests improved with repeated trials (two-factor ANOVA: p < 0.001 for trial factor) to similar extents in the aMCI and control groups with no significant interaction of the trial and group factors (p = 0.266 in CVLT-II and p = 0.239 in BVMT-R).SignificanceAmnestic MCI subjects have diminished STM but intact learning ability. Differences in STM of older adults with vs. without aMCI are more readily distinguished by word-verbal memory and/or visuospatial memory testing than digit-verbal memory testing.